Supplier Relationships to Family Firms - Rose, Christoph (Familienunternehmen und KMU,, 2018)
Christoph Rose provides a broader differentiation of the perspective on family-owned companies. In contrast to several studies that merely discuss family-owned companies and non-family companies, his analysis is based on family influence, so the dominating heterogeneity of family-owned companies in practice is taken into account. The author provides an empirical database that substantiates his statements and that is the first attempt to make the conceptional FIBER model of socio-emotional wealth suggested in literature accessible to empirical analysis. Contents Relationship Quality in Business to Business Customer-Supplier Relationships Supplier Relationships to Family Firms Conceptual Relationship Quality Framework Target Groups Researchers and students in the fields of distribution and sales, marketing and family business Family firm managers and suppliers The Author Dr. Christoph Rose wrote his dissertation under the supervision of Prof. Dr. Andreas Hack at the Institute of Family Business at WHU - Otto Beisheim School of Management, Vallendar. .